Issues and trends in science education: the shortage of qualified science teachers. - Mangrubang FR (American Annals of the Deaf)
SCIENCE TEACHERS are leaving their profession. They feel overwhelmed by the expectations and scope of the job and isolated and unsupported in their classrooms. They also feel that expectations are unclear. The statistics on turnover among new teachers are startling. School administrators, science teacher leaders, and teacher education programs can do much more to promote better preparation of science teachers and to recruit new teachers into science teaching. In particular, the author focuses on relevant research and on recommendations for educational researchers and policymakers interested in improving and retaining qualified science teachers in classrooms.